Gender diversity in the management field: Does it matter for research outcomes? - Wullum Nielsen, Mathias; Börjeson, Love (Research policy, 2019)
•Examines associations between gender diversity and research outcomes.•More than 25,000 management papers were analyzed.•Finds no effect of author-group gender composition on per-paper citation impact.•Documents consistent patterns of gender-related variations in research topics.•Argues that gender diversity may lead to broadened research agendas. This study examines the relationship between gender diversity and research outcomes. Existing research on the topic primarily focuses on how team gender diversity influences scholarly productivity in terms of citations and publication rates. Far less attention has been devoted to the question of how the intellectual contents of research disciplines change as they become more gender diverse. Drawing on a global sample of more than 25,000 management papers, we use natural language processing techniques, correspondence analysis and regression models to illuminate impact-, content- and status-related dimensions of gender diversity in management research. In regression models adjusting for geographical setting, institutional prestige and collaboration patterns, we find no discernable effects of team gender diversity on per-paper scientific impact. In contrast, our analyses converge to yield a broadly consistent pattern of gender-related variations in research focus: women are well-represented in social- and human-centered areas of management, while men comprise the vast majority in areas addressing more technical and operational aspects. Our findings corroborate recent sociological research suggesting that cultural norms and expectations are channeling women and men towards different areas of work and study. We argue that the broadened repertoire of perspectives, values and questions resulting from gender diversity may render management research more responsive to the full gamut of societal needs and expectations.